316L stainless steel designed to withstand intermediate temperature. (5th December 2017) - Saeidi, K.; Neikter, M.; Olsen, J.; Shen, Zhijian James; Akhtar, F.
Abstract: Austenitic stainless steel 316L was fabricated for withstanding elevated temperature by selective laser melting (SLM). Tensile tests at 800 °C were carried out on laser melted 316L with two different strain rates of 0.05 S − 1 and 0.25 S − 1 . The laser melted 316L showed tensile strength of approximately 400 MPa at 800 °C, which was superior to conventional 316L. Analysis of fracture surface showed that the 316L fractured in mixed mode, ductile and brittle fracture, with an elongation of 18% at 800 °C. In order to understand the mechanical response, laser melted 316L was thermally treated at 800 °C for microstructure and phase stability. X-ray diffraction (XRD) and Electron back scattered diffraction (EBSD) of 316L treated at 800 °C disclosed a textured material with single austenitic phase. SEM and EBSD showed that the characteristic and inherent microstructure of laser melted 316L, consisting of elongated grains with high angle grain boundaries containing subgrains with a smaller misorientation, remained similar to as-built SLM 316L during hot tensile test at 800 °C. The stable austenite phase and its stable hierarchical microstructure at 800 °C led to the superior mechanical response of laser melted 316L. Graphical abstract: Highlights: Laser melted 316L withstands 800 °C under tension determined by thermo-mechanical test. Tensile strength of 400 MPa with elongation of 18% at 800 °C Stable phase composition and fine microstructure with grains containing 1 μm cellular subgrains